Rest-to-Rest Attitude Naneuvers and Residual Vibration Reduction of a Finite Element Model of Flexible Satellite by Using Input Shaper - Setyamartana Parman; Hideo Koguchi (Shock and Vibration)
A three-dimensional rest-to-rest attitude maneuver of flexible spacecraft equipped by on-off reaction jets is studied. Equations of motion of the spacecraft is developed by employing a hybrid system of coordinates and Lagrangian formulation. The finite element method is used to examine discrete elastic deformations of a particular model of satellite carrying flexible solar panels by modelling the panels as flat plate structures in bending. Results indicate that, under an unshaped input, the maneuvers induce undesirable attitude angle motions of the satellite as well as vibration of the solar panels. An input shaper is then applied to reduce the residual oscillation of its motion at several natural frequencies in order to get an expected pointing precision of the satellite. Once the shaped input is given to the satellite, the performance improves significantly.